Challenges and suggestions for raising children with autism spectrum disorder: A literature review - Theary Sun; Kimkong Heng (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2025)
Being a parent is a journey that is both rewarding and challenging; however, this journey can be particularly challenging for parents who are raising a child with autism spectrum disorder (ASD). Drawing on secondary sources, this review article aims to synthesize findings from previous research to examine the key challenges encountered by parents of children with ASD. Key challenges identified are related to psychological, social, marital, physical, financial, and behavioral challenges. The review also discusses practical suggestions to mitigate these challenges, focusing on prioritizing well-being, building strong social networks, strengthening marital relationships, exploring different financial resources, and managing behavioral challenges. By discussing both the challenges and solutions, this review article provides valuable insights into how to raise a child with ASD, helping parents navigate this difficult journey with resilience and hope. The article concludes by discussing its limitations and providing suggestions for future research.